ANALISIS TEOLOGIS PEMAHAMAN GMAHK JEMAAT BARUS JULU TENTANG INTERPRETASI “MENGHUJAT ROH KUDUS” BERDASARKAN MARKUS 3:28,29 - O Wilden Efransa Ginting (Jurnal Koinonia, 2016)
In this study, the author examines the understanding of blaspheming the Holy Spiritis based on Mark 3:28, 29. The author of this research focuses on the Seventh-dayAdventists Church of Barus Julu, Karo. The study has a base with three mainindicators, namely; the role of the Holy Spirit, the concept of blasphemy of the HolySpirit and not be forgiven forever.This study is divided into two parts, namely the study of the theory and fieldresearch. The results of the study of the theory is about the role and work of theHoly Spirit, the concept and definition of blasphemy of the Holy Spirit never hasforgiveness forever and is guilty of an eternal sin.This study includes three parts: (1) What is the role and work of the Holy Spirit.Some experts say that the role of the Holy Spirit at the end of this age are verynumerous and important. Some of the Holy Spirit's role is very important of which isto help the saints in prayer, giving a new heart, give the gift of the Spirit, which leadsto Truth, helper and comforter, sensitize and convince; (2) Definition of blasphemyof the Holy Spirit. Experts claim that blaspheming the Holy Spirit that is resistingthe Holy Spirit works continuously and when the Holy Spirit had retreated fromhumans, so there is no repentance on human; (3) Never has forgiveness forever andis guilty of an eternal sin. The only unpardonable sin is blaspheming the Holy Spirit.The results of field research conducted through a questionnaire distributed to 34members of the church Seventh-day Adventist Church congregation Barus Julu,Karo, where the questionnaire contains 27-points statement generates a data it can beconcluded that the respondents have a poor understanding well in answering the firstindicator in a statement 3, 4 about the work Fatherhood different and in indicatorsboth in the statement 12 of blaspheming the Holy Spirit differ with blaspheming Godthe Father and Jesus, in a statement 13 of blaspheming the Spirit Ghost is said thatthe work of the Holy Spirit is the work of Satan.